Treatment Adherence Pattern among HIV/AIDS Patients Receiving Treatment in the ART Centre of a Tertiary Hospital in Kolkata - Atanu Biswas; Asok Kumar Mandal (Medsci Publications, 2016)
Background: WHO recommended at least 95% adherence to antiretroviral drugs for better outcome in terms of improved CD4 count, body weight, general well-being and decreased chance of drug resistance. This study was conducted with the objectives of describing socio-demographic profile and adherence pattern to ongoing regimens in adults with HIV/AIDS in a tertiary hospital in Kolkata, India. Methods: An observational, descriptive cross-sectional study was conducted on the adults receiving ART treatment. Patients above 15 years of age, who received at least one year of treatment before the day of the interview, comprise the study population. Sample size was 279. Information regarding socio-demographic profiles and the level of adherence to treatment in last one month and last one year were collected. The subjects were also asked about the reason behind the missed doses. Results: Majority of the subjects were male and belonged to 25-44 years of age group. Most of the subjects were from low socioeconomic status and had poor level of education. Adherence level of treatment in last one year was adequate in 93.9% subjects, whereas 98.6% subjects had adequate adherence level in last one month. Fear of side effects from the drugs and forgetfulness were the major reasons behind the missed doses. Conclusion: Emphasis should be given on awareness generation and proper counseling of the people with HIV/AIDS so as to maintain adequate adherence level of therapy improving their general well-being.